Efikasi Diri Akademik dan Tingkat Stres pada Mahasiswa Peserta Merdeka Belajar Kampus Merdeka - Annisa Julia Zulkarnain Gani; Narastri Insan Utami (Fakultas Tarbiyah dan Ilmu Keguruan, IAI Sultan Muhammad Syafiuddin, 2024)
Education is an essential part of an individual's life, and a significant initiative is the freedom of learning independent campus program. This government policy grants students the freedom to study outside their major for three semesters. However, this freedom has led to various issues, causing stress among participating students. One factor that can help address this stress is academic self-efficacy. This study aims to investigate the relationship between academic self-efficacy and stress levels among students in the among students participating in the freedom of learning independent campus. The hypothesis proposed is that there is a negative relationship between academic self-efficacy and stress levels. The study involves 156 students participating in the program. Data collection used an academic self-efficacy scale and a stress level scale. The data analysis technique used is the Pearson correlation. Based on the data analysis, the correlation coefficient (rxy) = -0.609 (p < 0.05) was obtained. The results indicate a negative relationship between academic self-efficacy and stress levels. From the calculation of the coefficient of determination (R2), it is found that academic self-efficacy contributes 37.1% to stress levels. Meanwhile, 62.9% of the factors influencing stress levels in students are due to other factors